UPAYA GURU MENGEMBANGKAN BUDAYA LITERASI DALAM PEMBELAJARAN DI KELAS AWAL SDN 12 ANGGREK - Mopangga, Bahtiar; Pomalingo, Samsi; Husain, Rustam I. (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to describe: (1) Teachers' efforts in developing a culture of literacy, (2) Supporting and inhibiting factors of a culture of literacy. This study uses a qualitative approach with data collection techniques used, namely interviews, observations, and document studies. The data analysis process is carried out using data collection, data condensation. Data presentation, and drawing conclusions. Testing the validity of the data using triangulation of methods and sources. The results of this study include: (1) Teachers' efforts in developing a culture of literacy that is applied include the creation of a supportive literacy environment, such as attaching pictures and texts in the classroom, and providing literacy facilities such as reading corners and libraries that make it easier for students to access reading., (2) Supporting and inhibiting factors of a culture of literacy, literacy facilities and an environment that supports a culture of reading. The active involvement of teachers in literacy activities, both before and after learning, also strengthens these efforts. However, the main challenges faced are student laziness and lack of parental support in supporting literacy activities at home. In addition, students tend to prefer digital information.